An Accelerated Algorithm Involving Quasi-$φ$-Nonexpansive Operators for Solving Split Problems (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, an algorithm of inertial type for approximating solutions of split equality fixed point problems involving quasi-$φ$-nonexpansivemaps is proposed and studied in the setting of certain real Banach spaces.Weak and strong convergence theorems are proved under some conditions.Some applications of the theorems are presented. The results presented extend and improve some existing results. Finally, some numerical illustrationsare presented to support our theorems and their applications.
Keywords: Fixed point; Quasi-$φ$-nonexpansive; Inertia.